Risk Aversion and the Choice Between Risky Prospects: The Preservation of Comparative Statics Results - Jewitt, Ian (Review of Economic Studies, 1987)
Most results in what can be termed the comparative statics of risk aversion are obtained when there is only one source of uncertainty. The primary example (which originally motivated the definition of risk aversion) is that more risk averse people are willing to pay a higher premium for insuring against risk. It is known that the results do not generally carry over when there is another source of uncertainty. The paper develops conditions under which comparative statics results are robust against the introduction of additional sources of uncertainty.